THE EARTHQUAKE SENSITIVITY ANALYSIS OF GALLIPOLI PENINSULA USING GEOGRAPHIC INFORMATION SYSTEMS (GIS) AND ANALYTIC HIERARCHY PROCESS (AHP) - Halid PEKTEZEL (Fırat University, 2019)
Earthquake is one of the forces of nature which leads to loss of life and property and cannot be predicted beforehand. Half of the Turkish territory is in the first-degree zone and 44% of the population lives in this zone. Inappropriate area selection for settlement may turn earthquake, an ordinary natural force, into a catastrophe. The quality and scope of the studies carried out at the present time have been increasing. The present studies have mostly been carried out using Geographic Information Systems (GIS). In this research it is aimed to realize the earthquake sensitivity analysis of Gallipoli Peninsula using Geographic Information Systems (GIS) and Analytic Hierarchy Process (AHP). Firstly, the earthquake risk of the zone has been disclosed. Afterwards, the other factors affecting earthquake sensitivity such as lithology, distance to fault line, the largest ground acceleration, hydrogeology, geographical formations, slopes and distance to rivers have been determined and their effect on the earthquake risk and sensitivity. The factors affecting earthquake sensitivity have been determined by classifying the studies and data concerning earthquakes. Various data obtained from different studies have been used in order to form the factor map. The formation of factor maps and image analyses have been carried out using ArcGIS / ArcMap 10.2 package programs. It has been found that the earthquake sensitivity in Gallipolis peninsula is high as 82,2 % (774,0 km²) of the territory. It can be concluded that the region is partially appropriate for settlement. It is thought that Gallipolis peninsula will become a center of attraction after the completion of Gallipoli Strait Bridge, which is to be finished in 2023. It is necessary to take the results of this study into consideration while deciding new settlement places in The Gallipolis peninsula, which is thought to have some changes in its social-economic status and population in the near future. ın order to minimize the loss of life and property during a probable earthquake the development of the settlement should be directed to areas with lower and middle sensitivity of earthquake. By the same token, the same case situation has been emphasized in the studies carried out for the region of Marmara. Therefore, more detailed application studies are needed. In the existing land use where the earthquake sensitivity is high necessary measure should be taken. The earthquake resistance analyses should be made for t